2015
DOI: 10.1074/jbc.m115.679852
|View full text |Cite
|
Sign up to set email alerts
|

Humanized Affinity-matured Monoclonal Antibody 8H9 Has Potent Antitumor Activity and Binds to FG Loop of Tumor Antigen B7-H3

Abstract: Background: B7-H3 is an immune inhibitory ligand and an antigen on many solid tumors. Results: Antibody 8H9 was humanized and affinity-matured, and its epitope was mapped to the FG loop of B7-H3. Conclusion: hu8H9 antibodies had potent antitumor activity and may modulate immune inhibitory properties of B7-H3. Significance: Antibodies were developed to target solid tumors and affect immune checkpoint blockade.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
79
0
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 89 publications
(82 citation statements)
references
References 64 publications
2
79
0
1
Order By: Relevance
“…IgG1 is the human isotype most effective at stimulating ADCC or CDC in humans and mice, and other anti-CD276 IgG1s have been shown to elicit ADCC in preclinical studies (Ahmed et al, 2015; Loo et al, 2012) suggesting that m276 could also have therapeutic activity on its own. However, preliminary studies in mice indicated that m276 had little, if any, anti-tumor activity.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…IgG1 is the human isotype most effective at stimulating ADCC or CDC in humans and mice, and other anti-CD276 IgG1s have been shown to elicit ADCC in preclinical studies (Ahmed et al, 2015; Loo et al, 2012) suggesting that m276 could also have therapeutic activity on its own. However, preliminary studies in mice indicated that m276 had little, if any, anti-tumor activity.…”
Section: Resultsmentioning
confidence: 99%
“…Another humanized antibody, 8H9, originally identified based on its selective reactivity with human tumors cells, was later found to recognize CD276 and is also in Phase I clinical trials (Ahmed et al, 2015; Modak et al, 2001). However, these mAbs recognize human but not rodent CD276 precluding an assessment of the contribution of CD276 positive tumor-associated stromal cells in therapeutic targeting, and potential toxicities caused by inappropriate targeting of CD276 positive normal cells in preclinical rodent models.…”
Section: Introductionmentioning
confidence: 99%
“…8H9 is a mAb specific to B7-H3 that demonstrated clinical success as an ADC following it being radiolabeled to iodine-131 ( 131 I) and administrated to patients with metastatic central nervous system neuroblastoma (49). 8H9 also distinguishes itself from other B7-H3 specific antibodies in that it binds to the FG loop of B7-H3, a region critical to its immunological function (50). Recently, 8H9 was humanized and affinity matured and maintained its ability to kill B7-H3 positive neuroblastoma cells in vitro .…”
Section: Clinical-translational Advancesmentioning
confidence: 99%
“…Two-fold and five-fold enhancements in killing were observed by the affinity matured and humanized 8H9 compared to the non-matured and chimeric generations, respectively. Furthermore, the mAb was labeled with 131 I and injected into athymic nude mice xenografted with human neuroblastoma and showed successful biodistribution to the tumor (50). Currently, clinical trials with radiolabeled 8H9 are ongoing in patients with peritoneal cancers, gliomas, and advanced central nervous system cancers (NCT01099644, NCT01502917, and NCT00089245).…”
Section: Clinical-translational Advancesmentioning
confidence: 99%
“…It is also being evaluated in combination with ipilimumab (anti-CTLA-4 mAb) or pembrolizumab (anti-PD-1 mAb) in safety studies of refractory cancers (trial NCT02381314 and NCI201501495). The murine mAb 8H9 was found to target an unknown antigen on many solid tumors, and only recently has this antigen been discovered to be B7-H3 [59]. Radioimmunoconjugated 8H9 with cytotoxic I131 is currently in phase I trials for central nervous system and peritoneal tumors (NCT01099644 and NCT01502917), and other groups are testing 8H9 with other toxic conjugates [60] in murine models.…”
Section: New Immune Checkpoints B7-h3 B7x and Hhla2mentioning
confidence: 99%